2017
DOI: 10.1039/c7gc01288h
|View full text |Cite
|
Sign up to set email alerts
|

Tandem dehydration–transfer hydrogenation reactions of xylose to furfuryl alcohol over zeolite catalysts

Abstract: Dehydration and transfer hydrogenation tandem reactions of xylose to furfuryl alcohol in water/isopropanol were performed on MFI, FAU and BEA zeolites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 24 publications
4
52
0
Order By: Relevance
“…An interesting effect that was studied in the article shows the role of isolated metal centers, which afford the production of xylitol, whereas the presence of sole acid sites leads to the formation of FUR. A following paper from the same research group reported a high selectivity to FuOH (75%) over a metal-free catalyst (zeolite beta) via MPV [82]. This high selectivity to FuOH was linked to the configuration of tetrahedral-framework Al centers tailored by the Al-O-Si bond distance and the characteristic typology of the catalyst.…”
Section: Formation Of Furfuryl Alcohol From Xylose In One-pot Reactionsmentioning
confidence: 95%
See 1 more Smart Citation
“…An interesting effect that was studied in the article shows the role of isolated metal centers, which afford the production of xylitol, whereas the presence of sole acid sites leads to the formation of FUR. A following paper from the same research group reported a high selectivity to FuOH (75%) over a metal-free catalyst (zeolite beta) via MPV [82]. This high selectivity to FuOH was linked to the configuration of tetrahedral-framework Al centers tailored by the Al-O-Si bond distance and the characteristic typology of the catalyst.…”
Section: Formation Of Furfuryl Alcohol From Xylose In One-pot Reactionsmentioning
confidence: 95%
“…Nevertheless, solid catalysts offer advantages such as easy recovery and regeneration. A reaction mechanism for the MPV reduction step was proposed by Paulino et al [82]. In the tandem reaction, xylose is dehydrated to FUR on the zeolite Brønsted acid sites.…”
mentioning
confidence: 99%
“…Figure 4 shows the FTIR spectrum of electrospun C-Zein and DES-Zein nanofibers. C-Zein showed a significant peak at 3,289 cm −1 due to -NH stretching, while DES- www.nature.com/scientificreports/ Zein showed intensive and broad stretching peak at 3,303 cm −1 due to the strong hydrogen bonding between -OH from Choline chloride/furfuryl-alcohol moiety and -NH from Zein polymer 15,16,22 . The intense bands at 2,875 cm −1 and 2,960 cm −1 due to the asymmetric and symmetric C-H stretching in the spectrum of DES-Zein nanofibers, which may be due to the induced dipole moment caused by the change in solvent polarity comparing to C-Zein nanofibers.…”
Section: Influence Of Electrospinning Parameters On Morphology Of Desmentioning
confidence: 99%
“…The mass 40 ± 0.2 mg of DES-Zein nanofibers was shacked in glass tube filled with 5 mL of Reactive black 5 dye solution at room temperature. Dye adsorption values were then checked at different intervals (0, 5,8,12,15,18,20, and 25) min 44,45 .…”
Section: Preparation Of Des-zein Nanofibersmentioning
confidence: 99%
“…To replace the use of H 2 gas and a noble metal, an alternative strategy of transfer hydrogenation with an alcohol (preferentially 2‐propanol) as a hydrogen source that relied on Meerwein–Ponndorf–Verley (MPV) reduction has been developed for the synthesis of furfuryl alcohol directly from xylose. Acidic zeolites with different framework topologies (i.e., MFI, FAU, and BEA) were used to catalyze the cascade conversion of xylose dehydration and successive transfer hydrogenation of furfural with 2‐propanol as a hydrogen donor in a mixture of water and 2‐propanol (1:1 v/v) at 130 °C . It was found that BEA zeolite afforded an excellent selectivity (i.e., 75 %) toward furfuryl alcohol at 12.5 % xylose conversion after 1 h. The authors noted that the BEA‐type topology, with a large 3D pore structure, along with tetrahedral Al species within the framework generated by Al−O−Si distances, were responsible for the remarkable catalytic performance of BEA zeolite.…”
Section: Catalytic Processes With Constant Carbon Numbermentioning
confidence: 99%